2019
DOI: 10.2166/wqrj.2019.042
|View full text |Cite
|
Sign up to set email alerts
|

Ecotoxicological study of landfill leachate treated in the ANAMMOX process

Abstract: The exacerbated production of solid residues represents a major problem in the management and handling of urban wastes. The by-product of stored municipal and industrial solid waste production is landfill leachate. Leachate is characterized by a high concentration of organic compounds, ammonia, and the presence of heavy metals. Because of its composition, this kind of wastewater can cause serious environmental pollution and should be treated to reduce its toxic effects. Increasingly, the interest is directed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…The pH effect was investigated; 100 mg • dm -3 of tetracycline solutions were prepared in the pH range (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12). After adjustment, the solutions were mixed with 0.3 g of adsorbent during 24 h at 298 K. The pH was adjusted by using 0.1 N of HCl or KOH according to the desired pH value.…”
Section: Ph Effectmentioning
confidence: 99%
See 1 more Smart Citation
“…The pH effect was investigated; 100 mg • dm -3 of tetracycline solutions were prepared in the pH range (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12). After adjustment, the solutions were mixed with 0.3 g of adsorbent during 24 h at 298 K. The pH was adjusted by using 0.1 N of HCl or KOH according to the desired pH value.…”
Section: Ph Effectmentioning
confidence: 99%
“…Therefore, the composition of leachates is very difficult to determine. Despite the complexity of the effluent, it is 1 Scientific and Technical Research Center in Physico-Chemical Analysis, PO box 384, Headquarters ex-Pasna Industrial area Bou-Ismail, zip code 42004 Tipaza, Algeria, phone +213(0)24325774, fax +213(0)24325774, ORCID: 0000-0002-1432-7237 2 LPCEMAE Laboratory, Faculty of Chemistry, Houari Boumediene University of Science and Technology (USTHB), PO box 32 ELALIA, Bab Ezzouar Algiers, Algeria, email: bhamdi_99@yahoo.fr, ORCID: 0000-0002-5502-1605 3 Controlled Porosity Materials Team, Institute of Materials Sciences of Mulhouse UMRCNRS 7361, University of Strasbourg, University of Haute Alsace, ENSCMu, 3 rue Alfred Werner, 68093 Mulhouse Cedex, France, email: jocelyne.brendle@uha.fr, ORCID: 0000-0001-5266-6224 possible to identify these xenobiotic compounds [9][10][11][12][13][14][15][16]: phenols, chlorinated aliphatic compounds, aromatic hydrocarbons, tetracycline, pesticides, and plasticizers.…”
Section: Introductionmentioning
confidence: 99%
“…This transformation occurs in the presence of carbon dioxide (CO2), which serves as the carbon source necessary for the development of the Anammox bacteria (see Eq. 1) [22]. NH4 + + 1.3H + + 1.32NO2 -+ 0.06HCO3 -→ 1.02N + 0.26NO3 -+ 2.03H2O + 0.06CH2O0.5N0.15 (1) [23] It has been suggested that to optimize the use of scarce resources, it is possible to implement procedures that facilitate the recovery and recycling of nutrients found in sewage, so minimizing any potential harm to the environment.…”
Section: Anaerobic Ammonium Oxidation Processmentioning
confidence: 99%
“…Annamox is particularly suited for the treatment of nitrogen-rich wastewaters, such as LFL. Anammox bacteria, converts ammonium into dinitrogen gas as depicted in Figure 6 by using ammonium nitrogen as an electron donor and nitrite as an electron acceptor under anoxic conditions [79]. It was demonstrated that treatment based on Anammox is promising for potential application in the elimination of nitrogen from LFL due to its cost-effectiveness (less aeration energy) and the high performance of denitrification [80].…”
Section: Post Treatment For Ammonia Removal In Landfill Leachatementioning
confidence: 99%